The functional shift in social media; prepositions and conjunction as a sample - ALANAZI, NUJUD ISMAIL; ABDUL JABAR, MOHD AZIDAN; HASSAN, ABDURRAUF; BIN MOHAMAD, ABULHALIM (Arab Journal for Sciences and Research Publishing, 2019)
Arabic language is exposed to many negative linguistic manifestations, such as the phenomenon of widespread grammatical error in social media. The aim of the current study is to monitor grammatical errorin in social media and to identify factors affecting mistakes for (prepositions, conjunctions). The study also seeks to investigate the impact of grammatical variation on the understanding and to detect the effect of grammatical erroron Level. In order to verify the validity of the hypotheses and to answer all the questions, the researcher used the statistical analytical descriptive method in order to obtain the study data. invention “Application third party” by the researcher to correct mistakes among people in social media. The study sample consist of only 200 sentences from (2016 to 2018). with many Arab political and social events occurring in this period, so the social media has become an important and influential medium in the Arab world. The main of results of research was descriptive and statistical results: The Mistake was just in conjunctions, prepositions; because the people used it misplaced. The mistake in the prepositions were %82, while the mistake in the conjunctions just %17.
Keywords: Functional displacement; Social media; Conjunctions; حروف الجر